1994
DOI: 10.1037/1061-4087.46.3.19
|View full text |Cite
|
Sign up to set email alerts
|

A motivational model for consulting with not-for-profit organizations: A study of church growth and participation.

Abstract: This study found support for the application of a theory of motivation to counseling churches regarding member enjoyment and involvement. The suitability of one of self-determination theory's assessment instruments to this type of consulting situation was also demonstrated. The research revealed a relationship between the level of experience of three categories of variables associated with intrinsically motivated behavior and the growth or non-growth of church membership, attendance, and giving. Organizational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 14 publications
0
16
1
Order By: Relevance
“…Other studies using a social determination theory approach have also demonstrated the importance of these dimensions, although within more specific domains, rather than for self-generated personal projects (e.g. Baard, 1994;Sarrazin et al, 2002;Miserandino, 1996;Vallerand et al, 1997). Outside this theoretical framework, studies using an expectancy-value approach have similarly demonstrated that both the expectation of success and the belief that an activity is consistent with a core part of one's actual or desired self are important to individual's choice of, and persistence with activities (Eccles & Wigfield, 2002).…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…Other studies using a social determination theory approach have also demonstrated the importance of these dimensions, although within more specific domains, rather than for self-generated personal projects (e.g. Baard, 1994;Sarrazin et al, 2002;Miserandino, 1996;Vallerand et al, 1997). Outside this theoretical framework, studies using an expectancy-value approach have similarly demonstrated that both the expectation of success and the belief that an activity is consistent with a core part of one's actual or desired self are important to individual's choice of, and persistence with activities (Eccles & Wigfield, 2002).…”
Section: Discussioncontrasting
confidence: 98%
“…Baard, 1994;Sarrazin et al, 2002;Sheldon & Bettencourt, 2002), it is of note that these studies have been in group-based contexts, such as church, sports teams and campus groups. When the array of activities that characterize people's lives are examined as a whole, it appears that relatedness loses its predictive value, at least when put alongside competence and integrity.…”
Section: Discussionmentioning
confidence: 99%
“…Fredricks et al (2002) found that the social benefits gained from participation in the sports and arts strongly influence adolescents' future engagement or disengagement. Interestingly, in our quantitative measures, neither real-time nor recalled togetherness was significantly correlated with desire to repeat the experience, which is somewhat at odds with other studies of activities in group settings (e.g., Baard, 1994;Sarrazin, Vallerand, Guillet, Pelletier, & Cury, 2002;Sheldon & Bettencourt, 2002). However, other research with youth has shown that belonging may sometimes fall away as a direct motivator if an activity provides integrity-related experiences and an avenue to express competence (Harré & Bullen, 2010;Ryan & Deci, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…According to self-determination theory (Deci & Ryan, 1985b;, opportunities to satisfy the three intrinsic needs will facilitate selfmotivation and effective functioning because they facilitate internalization of extant values and regulatory processes, and they facilitate adjustment because need satisfaction provides the necessary nutriments for human growth and development (Ryan, 1995). Jn contrast, thwarted satisfaction of the needs will undermine motivation and have maladaptive consequences (Baard, 1994; Ryan et al, 1996;Sheldon, Ryan, & Reis, 1996).…”
Section: Self-determination Theorymentioning
confidence: 99%